Poor understanding of allergen labelling by allergic and non‐allergic consumers - Holleman, Bregje C.; Os‐Medendorp, Harmieke; Bergh, Huub; Dijk, Liselotte M.; Linders, Yvette F.M.; Blom, W. Marty; Verhoeckx, Kitty C.M.; Michelsen‐Huisman, Anouska; Houben, Geert F.; Knulst, André C.; Lentz, Leo R. (Clinical and experimental allergy, 2021)
Background Understanding consumers’ interpretation of allergy information is crucial for effective food safety policies. We evaluated consumer understanding of allergy information on foods in controlled, experimental studies. Method Using 18 packaged foods, we evaluated consumer understanding of information about allergens in two experiments: First, a comparison of foods with no stated allergen versus allergen as a stated ingredient versus a precautionary allergen label (PAL); second, a comparison of three common variants of PAL. In each experiment, consumers with and without self‐reported food allergy were asked to estimate the risk of allergic reaction and to rate the comprehensibility of the allergen information. In the second experiment, consumers were also asked which form of PAL they preferred. Results Risk of reaction was assessed as high and low for foods with the allergen stated as ingredient, or without any mention of allergen. However, risk assessment for PAL varied and was judged as higher by non‐allergic than allergic participants (82% vs. 58%, p < .001). Understanding of risk associated with PAL also varied by health literacy (p < .001). Both allergic and non‐allergic consumers judged all forms of allergy information to be unclear, especially products with no allergy information for non‐allergic consumers. Products with a ‘Produced in a Factory’ PAL were perceived as less risky than ‘May contain’ or ‘Traces of’ PALs (p < .001), less than 40% of participants judged PAL information to be comprehensible, and participants preferred ‘May contain’ over the other PALs. Conclusion Both allergic and non‐allergic consumers find allergen information difficult to interpret on packaged foods and misunderstand PAL, incorrectly distinguishing different risk levels for different PAL wording. Clearer allergy information guidelines are called for, and the use of only one PAL wording is recommended.